Calculus 4: Function

Calculus Level 3

0 1 1 + a 2 2 a a d a \large \int_0^1 ~ \frac{1+a^2-2a}{\sqrt[]{a}} ~ \mathrm{d}a

If value of the above integral is of the form A B \dfrac{A}{B} , where A A and B B are coprime positive integers, find the value of A B A -B .


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Viki Zeta
Oct 1, 2016

Relevant wiki: Beta Function

I = 0 1 1 + a 2 2 a a d a = 0 1 a 1 2 ( 1 a ) 2 rewrite the integral = 0 1 a 1 2 1 ( 1 a ) 3 1 = 0 1 a p 1 ( 1 a ) q 1 where p = 1 2 and q = 3 Now, the above is of the form : 0 1 t y 1 ( 1 t ) x 1 d t Therefore, 0 1 t y 1 ( 1 t ) x 1 d t = B ( x , y ) ; B(x, y) represents Beta function I = B ( p , q ) = B ( 1 2 , 3 ) I = Γ ( p ) Γ ( q ) Γ ( p + q ) = Γ ( 1 2 ) Γ ( 3 ) Γ ( 1 2 + 3 ) = Γ ( 1 2 ) Γ ( 3 ) Γ ( 7 2 ) = π 2 15 π 8 = 16 15 = A B A B = 16 15 = 1 \displaystyle I = \int_0^1 \dfrac{1+a^2-2a}{\sqrt[]{a}} ~ da \\ \displaystyle = \int_0^1 a^{-\frac{1}{2}} \cdot (1-a)^2 ~~ \color{#3D99F6}{\boxed{\text{rewrite the integral}}} \\ \displaystyle = \int_0^1 a^{\frac{1}{2} - 1} \cdot (1-a)^{3-1} \\ \displaystyle = \int_0^1 a^{p-1} \cdot (1-a)^{q-1} ~~ \color{#3D99F6}{\boxed{\text{ where p = }\dfrac{1}{2} \text{ and q = 3}}} \\ \displaystyle \text{Now, the above is of the form : } \int_0^1 t^{y-1}(1-t)^{x-1} \, dt \\ \displaystyle \text{Therefore, } \int_0^1 t^{y-1}(1-t)^{x-1} \, dt = B(x, y) \text{; B(x, y) represents Beta function} \\ \displaystyle \therefore I = B(p, q) = B\left(\dfrac{1}{2}, 3\right) \\ \displaystyle I = \dfrac{\Gamma\left(p\right)\Gamma\left(q\right)}{\Gamma\left(p+q\right)} \\ \displaystyle ~~ = \dfrac{\Gamma\left(\dfrac{1}{2}\right)\Gamma\left(3\right)}{\Gamma\left(\dfrac{1}{2}+3\right)} \\ \displaystyle ~~ = \dfrac{\Gamma\left(\dfrac{1}{2}\right)\Gamma\left(3\right)}{\Gamma\left(\dfrac{7}{2}\right)} \\ \displaystyle ~~ = \dfrac{\sqrt[]{\pi}\cdot2}{\dfrac{15\sqrt[]{\pi}}{8}} \\ \displaystyle ~~ = \dfrac{16}{15} \\ \displaystyle ~~ = \dfrac{A}{B} \\ \displaystyle \boxed{\therefore A-B = 16 - 15 = 1}

___________________________________________________________________________________ \text{\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_\_}

Now, finding values of Gamma functions.

Γ ( 1 2 ) = t = 0 + t 1 2 1 e t d t = t = 0 + e t t d t , y = t ; d y = d t 2 t Γ ( 1 2 ) = 2 y = 0 + e y 2 d y = y = + e y 2 d y = π . Γ ( x + 1 ) = x Γ ( x ) For x = 5 2 Γ ( 7 2 ) = 5 2 Γ ( 5 2 ) For x = 3 Γ ( 5 2 ) = 3 2 Γ ( 3 2 ) Γ ( n 2 ) = ( n 2 ) ! ! π 2 ( n 1 ) 2 Γ ( 3 2 ) = ( 1 ) ! ! π 2 ( 2 ) 2 = π 2 Γ ( 5 2 ) = 3 2 Γ ( 3 2 ) = 3 π 4 Γ ( 7 2 ) = 5 2 5 2 Γ ( 5 2 ) = 5 2 3 π 4 = 15 π 8 \Gamma\left(\frac{1}{2}\right)=\intop_{t=0}^{+\infty}t^{\frac{1}{2}-1}e^{-t}dt=\intop_{t=0}^{+\infty}\frac{e^{-t}}{\sqrt{t}}dt, \\ y = \sqrt[]{t}; dy=\frac{dt}{2\sqrt{t}} \\ \Gamma\left(\frac{1}{2}\right)=2\intop_{y=0}^{+\infty}e^{-y^{2}}dy=\intop_{y=-\infty}^{+\infty}e^{-y^{2}}dy=\sqrt{\pi}. \\ \Gamma\left(x+1\right) = x\Gamma\left(x\right) \\ \text{For x =} \dfrac{5}{2} \\ \Gamma\left(\dfrac{7}{2}\right) = \dfrac{5}{2}\Gamma\left(\dfrac{5}{2}\right) \\ \text{For x = 3}\\ \Gamma\left(\dfrac{5}{2}\right) = \dfrac{3}{2}\Gamma\left(\dfrac{3}{2}\right) \\ \Gamma\left(\dfrac{n}{2}\right) = \dfrac{(n-2)!!\sqrt[]{\pi}}{2^{\frac{(n-1)}{2}}} \\ \Gamma\left(\dfrac{3}{2}\right) = \dfrac{(1)!!\sqrt[]{\pi}}{2^{\frac{(2)}{2}}} \\ ~~ = \dfrac{\sqrt[]{\pi}}{2}\\ \therefore \Gamma\left(\dfrac{5}{2}\right) = \dfrac{3}{2}\Gamma\left(\dfrac{3}{2}\right) \\ ~~ = \dfrac{3\pi}{4} \\ \boxed{\therefore \Gamma\left(\dfrac{7}{2}\right) = \dfrac{5}{2}\dfrac{5}{2}\Gamma\left(\dfrac{5}{2}\right) = \dfrac{5}{2} \cdot \dfrac{3\pi}{4} = \dfrac{15\pi}{8}}

There is a simpler way. Just use u-substitution.

Chew-Seong Cheong - 4 years, 8 months ago

Log in to reply

Yeah I saw other solutions but this problem is actually based on beta function, so my solution solves it that way

Viki Zeta - 4 years, 8 months ago

Log in to reply

It is better to show others the easiest way to solve a problem.

Chew-Seong Cheong - 4 years, 8 months ago

I = 0 1 1 + x 2 2 x x d x = 0 1 ( x 1 ) 2 x d x Let u 2 = x , 2 u d u = d x = 0 1 2 u ( u 2 1 ) 2 u d u = 0 1 2 ( u 2 1 ) 2 d u = 2 0 1 ( u 4 2 u 2 + 1 ) d u = 2 ( 1 5 2 3 + 1 ) = 16 15 \begin{aligned} I & = \int_0^1 \frac {1+x^2-2x}{\sqrt x} dx \\ & = \int_0^1 \frac {(x-1)^2}{\sqrt x} dx & \small \color{#3D99F6}{\text{Let }u^2=x, \ 2u \ du = dx} \\ & = \int_0^1 \frac {2u(u^2-1)^2}u du \\ & = \int_0^1 2(u^2-1)^2 \ du \\ & = 2 \int_0^1 (u^4-2u^2+1) \ du \\ & = 2\left(\frac 15 - \frac 23 + 1 \right) \\ & = \frac {16}{15} \end{aligned}

A B = 16 15 = 1 \implies A - B = 16 - 15 = \boxed{1}

Steven Chase
Oct 1, 2016

It's also possible to do this in a very pedestrian way.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...